2019
DOI: 10.1371/journal.pmed.1002926
|View full text |Cite
|
Sign up to set email alerts
|

Preconception diabetes mellitus and adverse pregnancy outcomes in over 6.4 million women: A population-based cohort study in China

Abstract: BackgroundDiabetes mellitus (DM) increases the risk of adverse maternal and neonatal outcomes, and optimization of glycemic control during pregnancy can help mitigate risks associated with diabetes. However, studies seldom focus precisely on maternal blood glucose level prior to pregnancy. We aimed to evaluate the associations between preconception blood fasting plasma glucose (FPG) level and subsequent pregnancy outcomes.Methods and findingsWe conducted a population-based retrospective cohort study among 6,44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 23 publications
3
69
2
Order By: Relevance
“…The pooled prevalence of adverse birth outcome among diabetic women in Ethiopia is 5.3% higher as compared with its counterpart [95% CI; 1.61, 17.41]. This is in line with the study done in Kathmandu Medical College Teaching Hospital 8.89% [39], Kulashekaram 13.4% [40], Dharan 10.66% [41], Saudi Arabia 2.7% [37], Denmark 2.5% [10], and China 15 .6% [42], This could be due to the health care package and system towards maternal and newborn health is similar between the countries. In addition, different countries are realizing different strategies and preventive measures to reduce the resulting adverse birth outcome.…”
Section: Discussionsupporting
confidence: 73%
“…The pooled prevalence of adverse birth outcome among diabetic women in Ethiopia is 5.3% higher as compared with its counterpart [95% CI; 1.61, 17.41]. This is in line with the study done in Kathmandu Medical College Teaching Hospital 8.89% [39], Kulashekaram 13.4% [40], Dharan 10.66% [41], Saudi Arabia 2.7% [37], Denmark 2.5% [10], and China 15 .6% [42], This could be due to the health care package and system towards maternal and newborn health is similar between the countries. In addition, different countries are realizing different strategies and preventive measures to reduce the resulting adverse birth outcome.…”
Section: Discussionsupporting
confidence: 73%
“…Although screening of asymptomatic individuals to identify those with prediabetes or diabetes might seem reasonable, rigorous clinical trials to prove the effectiveness of such screening have not been conducted and are unlikely to occur. Based on a population estimate, diabetes in women of childbearing age is underdiagnosed (76). Employing a probabilistic model, Peterson et al (77) demonstrated cost and health benefits of preconception screening.…”
Section: Screening and Testing For Prediabetes And Type 2 Diabetes Inmentioning
confidence: 99%
“…Macrosomia is defined as a neonatal birth weight greater than or equal to 4000 g [1], which is a risk factor for adverse maternal and fetal perinatal outcomes [2]. Mothers of newborns with macrosomia are at an increased risk of prolonged labor, labor augmentation with oxytocin, cesarean delivery, abnormal hemorrhage, infection, and perineal trauma [3], while macrosomic newborns have a greater risk for perinatal asphyxia, meconium aspiration, shoulder dystocia, and death [2,4,5].…”
Section: Introductionmentioning
confidence: 99%